The operating characteristic of free public 'Bas Selangorku' in Shah Alam - Muhammad Amirul Hadi, Zainal Abidin (2016)
Transport was key requirement of human to travel from one place to another. State government of Selangor makes an effort to increasing the attractiveness of public transport by providing free public "Bas SelangorKu‟ in Shah Alam. If the operation of free public "Bas SelangorKu‟ was success, maybe the government can expand the service to the overall Selangor district. Furthermore, the main government also can take the opportunity to implant this service to all state in Malaysia. The purpose of this research was to obtain the operating characteristic and passenger satisfaction towards service of free public "Bas SelangorKu‟. The service starts to operate in 1st July 2015. The data for the operating characteristic are collected during bus trip. Meanwhile, as for the service frequency, the data was recorded by staying stationary at the middle path station. For passenger satisfaction, questionnaire will be distributed among the user of "Bas SelangorKu‟. All data for operating characteristic and passenger satisfaction will be analyzed statically. From the results showed, there are quite high demands in public that used "Bas SelangorKu‟ and respondents provide a good perception of the quality of the service given. However, for the matter of time, there are quite a number of passengers who are not satisfied with the service In addition, this research also reviews if the free public "Bas SelangorKu‟ operations can be the backbone of the existing public transport in Shah Alam. Through the end of the research, some suggestion are made to improve the operation of "Bas SelangorKu‟ in Shah Alam to ensure that the level of service are in line with other free public transport in the other developed countries.